EFEK VARIASI FAKTOR AIR SEMEN TERHADAP KUAT GESER PASANGAN DAN POLA KERUSAKKAN GESER PASANGAN BETON RINGAN AERASI MENGGUNAKAN THIN BED MORTAR - Faqih Ma’arif, Candra Widiantoro (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
This research aims to investigate the capacity of shear strength Autoclaved Aerated Concrete using thin bed mortar as an adhesive with variations of water cement ratio and determine the crack pattern. This research was conducted in the laboratory of building materials, Department of Civil Engineering and Planning, Faculty of Engineering, Yogyakarta State University. The test object 20 x10x10cm in dimension. The adhesive material was used thin bed mortar with variety of water cement ratio 0.15; 0.20; and 0.25 respectively. The test results showed that the shear strength average with f.a.s 0.15 ; 0.20 ; and 0.25 were 0,243 MPa; 0.269 MPa ; and 0,270 MPa; The crack pattern is combination failure.